South Africa : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2004)
This Selected Issues paper reviews the status and potential impacts of HIV/AIDS in South Africa. It draws on demographic projections and economic studies, and summarizes the official policy response and actions taken by the nongovernmental and business communities. It presents some stylized facts on property price developments in South Africa, and reviews briefly the link between asset price developments and economic activity. It also looks at the ability of policymakers to identify asset price booms.